PENGARUH KUALITAS PELAYANAN DAN DISIPLIN KERJA KARYAWAN BIRO ADMINISTRASI UMUM TERHADAP KEPUASAN MAHASISWA - YOGI YUNANTO (Jurnal Akademika, 2017)
The research approach used in the procurement of this research is quantitative dekskiptifapproach. This method is used to collect and interpret data through the collection, compileand analyze the data so as to provide a clear picture of the Effect of Service Quality andWork Discipline Employees Public Administration Bureau of Student Satisfaction.Multiple linear regression analysis is used to know the influence of service quality andemployee discipline to student satisfaction.The variable of service quality (X1) simultaneously gives significant effect to studentsatisfaction at University X with probability value b1 is 0.017 less than 0.05. Employeediscipline variable (X2) simultaneously give a significant influence to student satisfaction atUniversity X with probability value b2 is 0,031 smaller than 0,05. The service qualityvariable (X1) has regression coefficient (β) equal to 0,149, employee work discipline (X2)equal to 0,123, hence can be said that service quality variable (X1) have dominant influenceto student satisfaction at Universitas X.Keywords: Service Quality, Employee Discipline, Student Satisfaction